Strategi Menjaga Kesehatan Mata Anak SD Di Era Digital - Alexei Blagov; Amanda Vivi Sefianti; Hawa, Anni (JANACITTA, 2023)
Abstract The development of digital technology has brought significant changes to the lifestyle of elementary school (SD) children. The use of electronic devices such as smartphones, tablets and computers has become an integral part of daily work. However, it is increasingly important to be aware of the negative impact of excessive screen exposure on children's eye health. The aim of this research is to identify effective strategies for maintaining the eye health of elementary school children in the digital era. In short, it can be said that maintaining the eye health of elementary school children in the digital era is a challenge that requires serious attention. The data collection technique involves collecting several previous studies to answer strategies for maintaining eye health for elementary school children in the digital era. The research results are that with an approach that includes education, supervision and adequate rest, we can mitigate the negative impact of screen exposure on children's eye health. It is hoped that the results of this research will provide valuable guidance for parents, teachers and relevant stakeholders to protect children's eye health in an increasingly digital era.   Abstrak Perkembangan teknologi digital membawa perubahan signifikan pada gaya hidup anak sekolah dasar (SD). Penggunaan perangkat elektronik seperti smartphone, tablet, dan komputer sudah menjadi bagian tak terpisahkan dalam pekerjaan sehari-hari. Namun, semakin penting untuk mewaspadai dampak negatif paparan berlebihan layar tersebut terhadap kesehatan mata anak. Tujuan dari penelitian ini adalah untuk mengidentifikasi strategi efektif untuk menjaga kesehatan mata anak sekolah dasar di era digital. Secara singkat dapat dikatakan bahwa menjaga kesehatan mata anak Sekolah Dasar di era digital merupakan tantangan yang memerlukan perhatian serius. Teknik pengumpulan data dengan cara mengumpulkan beberapa penelitian terdahulu untuk menjawab strategi menjaga kesehatan mata anak SD di era digital. Hasil penelitian yakni dengan pendekatan yang mencakup edukasi, pengawasan dan istirahat yang cukup, kita dapat memitigasi dampak negatif paparan layar terhadap kesehatan mata anak. Hasil penelitian ini diharapkan dapat memberikan panduan berharga bagi orang tua, guru, dan pemangku kepentingan terkait untuk melindungi kesehatan mata anak-anak di era yang semakin digital.